2019
DOI: 10.3390/ma12101663
|View full text |Cite
|
Sign up to set email alerts
|

Super-Toughed PLA Blown Film with Enhanced Gas Barrier Property Available for Packaging and Agricultural Applications

Abstract: Polylactic acid (PLA) holds enormous potential as an alternative to the ubiquitous petroleum-based plastics to be used in packaging film and agricultural film. However, the poor viscoelastic behavior and its extremely low melt strength means it fails to meet the requirements in film blowing processing, which is the most efficient film processing method with the lowest costs. Also, the PLA’s brittleness and insufficient gas barrier properties also seriously limit PLA’s potential application as a common film mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…PLA and its blends have gained a privileged position in the polymer industry as it shows balanced properties (mechanical, thermal, barrier, physical and so on) with an everyday most competitive price [29,30,31]. Today it is possible to find PLA in a wide variety of industrial applications that include automotive, construction and building, packaging, houseware and so on [32,33,34,35,36], Behera et al [37] proposed that by controlling the manufacturing process, the properties of PLA could be tailored e.g., by lowering M w and the glass transition temperature (T g ). On the other hand, PLA is one of the most widely used material employed for fused deposition modeling (FDM) for 3D printed parts for whatever industry [38,39,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…PLA and its blends have gained a privileged position in the polymer industry as it shows balanced properties (mechanical, thermal, barrier, physical and so on) with an everyday most competitive price [29,30,31]. Today it is possible to find PLA in a wide variety of industrial applications that include automotive, construction and building, packaging, houseware and so on [32,33,34,35,36], Behera et al [37] proposed that by controlling the manufacturing process, the properties of PLA could be tailored e.g., by lowering M w and the glass transition temperature (T g ). On the other hand, PLA is one of the most widely used material employed for fused deposition modeling (FDM) for 3D printed parts for whatever industry [38,39,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Light transmittance plays an important role in agricultural film production, which influences the growth of plants as the photosynthesis of plants mainly absorb visible light at the wavelength of 400–700 nm. PDLA-g-PEG-g-PDLA(DPD) triblock polymer and Polyethylene glycol (PEG) are introduced to the PLLA matrix by melt compounding process [ 103 ]. The agriculture film have been produced from PLLA/DPD/PEG-10 film presented highly transparent (T% = 75.84%) with light transmittance property similar to PE (T% = 77.42%) under 700 nm light wavelengths.…”
Section: Pla-based Biopolymer As Packaging Materialsmentioning
confidence: 99%
“…As a suitable plasticizer, PEG can be melt-blended with PLA to improve the degradation rate, crystallization kinetics and mechanical properties of PLA [ 24 26 ]. Jiang et al [ 27 ] used melt blending to add PEG to enhance the toughness and gas barrier properties of PLA for use in disposable packaging and agricultural films. Their results showed that adding 10 wt% PEG can greatly improve the toughness and gas barrier ability of PLA film without losing its film-blowing stability.…”
Section: Introductionmentioning
confidence: 99%